Behavioral phenotype of 49, XXXXY syndrome: Presence of anxiety‐related symptoms and intact social awareness. Issue 5 (21st February 2020) - Lasutschinkow, Patricia C.; Gropman, Andrea L.; Porter, Grace F.; Sadeghin, Teresa; Samango‐Sprouse, Carole A.
Abstract: 49, XXXXY is a rare X and Y chromosome variation that occurs in 1:85, 000 to 1:100, 000 live male births and is notable for variable motor, speech, and behavioral deficits. Case studies have described boys with this disorder as shy, impulsive, and aggressive with low frustration tolerances; however, previous studies have been limited due to cohort size. This study reports on the largest cohort of boys with 49, XXXXY to date with an emphasis on the prevalence of anxiety‐related symptoms and sociability from preschool to adolescence. The Child Behavior Checklist, Behavior Rating Inventory of Executive Function, 2nd edition, and Social Responsiveness Scale, 2nd edition were completed by parents on a cohort of 69. The cohort demonstrated deficits in social cognition and communication beginning in preschool, however, presented with consistent social awareness and motivation for social activities not previously appreciated in this disorder. In addition, signs of anxiety presented during preschool years and increased in severity with age, particularly in internalizing problems. Boys with 49, XXXXY presented with wide behavioral variability across all ages and domains. Further research into the potential influences of culture, birth order, biological treatment, and frequency of services is needed to better define the behavioral phenotype of children with this disorder.